Covid-19: Development of an Online Learning System with computer mediated communication is a solution? - Enjang AS; Mukhlis Aliyudin; Sarbini Sarbini (UIN Sunan Gunung Djati, 2022)
The Covid-19 period was the hardest hit, and Indonesia was no exception. The social impacts that occur in the community include many things, one of which is in education, which makes students, teachers, and stakeholders have to move quickly to find real solutions. The Indonesian government 2020 has issued a policy to learn from, but many are still not ready to change the old pattern (offline) into a new pattern (Online)—using combined approach research between qualitative and quantitative (Mix Method). This research was conducted at UIN Sunan Gunung Djati Bandung. This study aims to improve/develop the existing Learning Management System (LMS) to be more effective and efficient. There are no students who are constrained in using the LMS in the future, both from a social and technical perspective.